Administration of gamma‐hydroxybutyrate instead of beta‐hydroxybutyrate to a liver transplant recipient suffering from propionic acidemia and cardiomyopathy: A case report on a medication prescribing error. Issue 1 (3rd January 2020) - Tuchmann‐Durand, Caroline; Thevenet, Eloise; Moulin, Florence; Lesage, Fabrice; Bouchereau, Juliette; Oualha, Mehdi; Khraiche, Diala; Brassier, Anaïs; Wicker, Camille; Gobin‐Limballe, Stéphanie; Arnoux, Jean‐Baptiste; Lacaille, Florence; et al.
Abstract: Beta‐hydroxybutyrate (BHB) is a synthetic ketone body used as an adjuvant energy substrate in the treatment of patients with metabolic cardiomyopathy. A medication prescribing error led to the administration of the general anesthetic sodium gamma‐hydroxybutyrate (GHB) instead of sodium BHB in a liver transplant recipient with propionic acidemia and cardiomyopathy, causing acute coma. A 15‐year‐old boy suffering from neonatal propionic acidemia underwent liver transplantation (LT) for metabolic decompensation and cardiomyopathy (treated with cardiotropic drugs and BHB) diagnosed a year previously. The patient had been rapidly extubated after LT, and was recovering well. Eight days after LT, the patient suddenly became comatose. No metabolic, immunological, hypertensive, or infectious complications were apparent. The brain magnetic resonance imaging and electroencephalography results were normal. The coma was soon attributed to a medication prescribing error: administration of GHB instead of BHB on day 8 post‐LT. The patient recovered fully within a few hours of GHB withdrawal. The computerized prescription system had automatically suggested the referenced anesthetic GHB (administered intravenously) instead of the non‐referenced ketone body BHB, triggering coma in our patient. A computerized prescription system generated a medication prescribing error for a rare disease, in which the general anesthetic GHB was mistaken for the nonreferenced energy substrate BHB.